Schelling, Zizek, Baudrillard: the spectral logic - Carrasco-Conde, Ana (Anales del Seminario de Historia de la Filosofía, 2014)
The article tries to analyze the impact of our time of “society of the spectacle” (Debord) in the construction of the historical realities. For this, proposals from S. Zizek and J. Baudrillard about the Real, the reality and the simulacrum will be analyzed, using some approaches to the philosophy of F.W.J. Schelling.